Climate change and sustainable development : mitigation and adaptation - Streimikiene, Dalia; Mikalauskiene, Asta (CRC Press, 2021)
"Focuses on the linkage between climate change threats and sustainable development goals. It analyses the policies of climate change mitigation and adaptation from an economic point of view by addressing globalization, international trade, and business opportunities and challenges. Based on extended research on energy, transport, agriculture, etc., the case studies included are on business opportunities linked to mitigation and adaptation actions; from European Union greenhouse gas emission trading, to climate change adaptation policies in developing countries. It presents a framework for the harmonization of climate and sustainable development policies and their mutual outcomes"--